Experimental life cycle of Philophthalmus gralli (Trematoda: Philophthalmidae) in Venezuela - Díaz, Marcos T (2002)
Descriptions of the miracidium, mother redia, daughter redia, grandaughter redia, cercaria, metacercaria and adult stages of Philophthalmus gralli Mathis and Leger,1910 recovered from experimental infections are presented. The intermediate host, Melanoides tuberculata, was collected from freshwater rivulets in Aguasanta and Yaguracual, Sucre State, Venezuela. Chicken were orally infected with cercariae and metacercariae, and metacercariae were introduced directly into the eyes by pipette. Both processes of infection produced adult worms. This is a new geographical record for P. gralli.